Performance of enhanced geothermal system (EGS) in fractured geothermal reservoirs with CO2 as working fluid. (April 2019) - Guo, Tiankui; Gong, Facheng; Wang, Xiaozhi; Lin, Qiang; Qu, Zhanqing; Zhang, Wei
Highlights: The three-dimensional (3D) model composed of discrete fractures was presented. Water and CO2 were compared to evaluate their efficiency in EGS. A thermal–hydraulic-mechanical (THM) coupled model was proposed in EGS. The sensitivity analysis of fracturing parameters was carried out. Abstract: Creating an open, connected fracture by hydraulic stimulation is vital to heat mining in an enhanced geothermal system (EGS). The existence of natural fractures, which seriously affects the development pattern, can complicate the hydraulic fractures. Different fracture propagation patterns of hydraulic fracturing can be achieved through different fracturing processes under certain natural fracture scales. Besides, CO2 has attracted a lot of attention as working fluid because of its superior hydrothermal properties and CO2 geological storage. At present, the study of EGS for fractured geothermal reservoirs with CO2 as working fluid is quite limited. In this paper, we firstly presented a three-dimensional (3D) thermal–hydraulic-mechanical (THM) coupled model to analyze performance of EGS in fractured geothermal reservoirs with different natural fractures scales, reservoir stimulation scales, and working fluids (water and CO2 ), aimed to guide reservoir stimulation and fracture parameter design. The results are showed as follows: If not forming connected fractures, the existence of natural fractures would cause fluid loss, an increase in natural fracture density by 0.4%, and the heat extraction rate decreases 0.06 MW on average; Forming connected fractures in the foundation of natural fractures would increase the output flow rate, so the reservoir stimulation scale increases by 0.85% and the heat extraction rate increases 0.2 MW; CO2 has better heat extraction properties than water due to its lower viscosity, greatly improving the production efficiency. Combining the hydraulic fracture conductivity tests creatively, the sensitivity analysis of fracturing parameters is studied. The heat extraction rate decreases with the increase in fracture aperture and fracture permeability. Under certain closure pressure (40 MPa in this paper), the best ceramsite proppant concentration and proppant size are 5 kg/m 2 and 100 mesh, respectively, and the corresponding fracture conductivity is 1.6 μm 2 cm.